Mortality and its predictors among antiretroviral therapy naïve HIV-infected individuals with CD4 cell count ≥350 cells/mm3 compared to the general population: data from a population-based prospective HIV cohort in Uganda - Ben Masiira; Kathy Baisley; Billy N. Mayanja; Patrick Kazooba; Dermot Maher; Pontiano Kaleebu (Taylor & Francis Group, 2014)
Background: Evidence exists that even at high CD4 counts, mortality among HIV-infected antiretroviral therapy (ART) naïve individuals is higher than that in the general population. However, many developing countries still initiate ART at CD4 ≤350 cells/mm3. Objective: To compare mortality among HIV-infected ART naïve individuals with CD4 counts ≥350 cells/mm3 with mortality in the general Ugandan population and to investigate risk factors for death. Design: Population-based prospective HIV cohort. Methods: The study population consisted of HIV-infected people in rural southwest Uganda. Patients were reviewed at the study clinic every 3 months. CD4 cell count was measured every 6 months. Rate ratios were estimated using Poisson regression. Indirect methods were used to calculate standardised mortality ratios (SMRs). Results: A total of 374 participants with CD4 ≥350 cells/mm3 were followed for 1,328 person-years (PY) over which 27 deaths occurred. Mortality rates (MRs) (per 1,000 PY) were 20.34 (95% CI: 13.95-29.66) among all participants and 16.43 (10.48-25.75) among participants aged 15-49 years. Mortality was higher in periods during which participants had CD4 350-499 cells/mm3 than during periods of CD4 ≥500 cells/mm3 although the difference was not statistically significant [adjusted rate ratio (aRR)=1.52; 95% CI: 0.71-3.25]. Compared to the general Ugandan population aged 15-49 years, MRs were 123% higher among participants with CD4 ≥500 cells/mm3 (SMR: 223%, 95% CI: 127-393%) and 146% higher among participants with CD4 350-499 cells/mm3 (246%, 117%-516). After adjusting for current age, mortality was associated with increasing WHO clinical stage (aRR comparing stage 3 or 4 and stage 1: 10.18, 95% CI: 3.82-27.15) and decreasing body mass index (BMI) (aRR comparing categories ≤17.4 Kg/m2 and ≥18.5 Kg/m2: 6.11, 2.30-16.20). Conclusion: HIV-infected ART naïve individuals with CD4 count ≥350 cells/mm3 had a higher mortality than the general population. After adjusting for age, the main predictors of mortality were WHO clinical stage and BMI.